Mast cells can produce transforming growth factor β1 and promote tissue fibrosis during the development of Sjögren’s syndrome-related sialadenitis - Kaieda, Shinjiro; Fujimoto, Kyoko; Todoroki, Keita; Abe, Yushi; Kusukawa, Jingo; Hoshino, Tomoaki; Ida, Hiroaki (Modern rheumatology, 2022)
This study investigated the associations of mast cells with immune-mediated inflammation and fibrosis in patients with primary Sjögren's syndrome (pSS); it also explored the underlying pathophysiology of pSS-related sialadenitis. Twenty-two patients with pSS and 10 patients with sicca (control individuals) underwent labial salivary gland biopsies. Sections were subjected to staining and immunofluorescence analyses. HMC-1 human mast cells were cocultured with fibroblasts in vitro; fibroblasts were also grown in HMC-1 conditioned medium. mRNA levels of collagen Type I (Col1a) and transforming growth factor (TGF)β1 were analysed in cultured cells. Mast cell numbers in labial salivary glands were significantly greater in patients with pSS than in control individuals. In salivary glands from patients with pSS, mast cell number was significantly correlated with fibrosis extent; moreover, mast cells were located near fibrous tissue and expressed TGFβ1. Col1a and TGFβ1 mRNAs were upregulated in cocultured fibroblasts and HMC-1 cells, respectively. Fibroblasts cultured in HMC-1 conditioned medium exhibited upregulation of Col1a mRNA; this was abrogated by TGFβ1 neutralizing antibodies. Mast cell numbers were elevated in patients with pSS-related sialadenitis; these cells were located near fibroblasts and expressed TGFβ1. TGFβ1 could induce collagen synthesis in fibroblasts, which might contribute to fibrosis.